Syllable Effects in a Fragment Detection Task in Italian Listeners - Caroline eFloccia (Frontiers in Psychology, 2012)
In the line of the monitoring studies initiated by Mehler et al. (1981), a group of Italian listeners were asked to detect auditory CV and CVC targets in carrier words beginning with a CV, a CVC or a CVG (G = geminate) syllable with variable initial syllable stress. By slowing participants reaction times, using both catch and foil trials, a syllable effect was found, partially modulated by participants’ speed but not by stress location. When catch trials were removed in a second experiment the syllable effect was not observed, even if reaction times were similar to that of the first experiment. We discuss these data in relation to the language transparency hypothesis and the nature of the pivotal consonant.